Active Learning and Competency Preconditioning Strengthen Osteopathic Medical Student Performance, Physician Attributes, and Competency Assessments - Vivek R Joshi; Michael J Younger; Bhargavi Joshi (Tabriz University of Medical Sciences, 2021)
Background: Medical education has been reliant on didactic lectures, which are predominantly teacher-centered learning. Competency-based education was introduced in North America and with this came a paradigm shift in how schools conceptualize curricula and measure learning outcomes. This modern approach started a change away from traditional lecture-based and teacher-centered curricula to a more student-centric approach using various tools. Competency based education is widely regarded as an outcome-based approach to design, implement and evaluate the curriculum using widely accepted competencies. Authorities recommend seven core competencies which have various indicators to address student performance. The main purpose of this research is to utilize active learning tools to enhance this approach and then assess competencies in the first year of medical school to improve academic outcomes as well as exposing students to competency domains on which they will be assessed and to ultimately create a complete physician. Methods: The study was conducted at a medical school during the first semester of medical school and included 145 students. Various active learning tools, such as modified case-based learning, quizzes, and case discussions, were used to assess competency in a biochemistry and genetics course, and these were compared to questions based on concepts delivered by the traditional lecture method. Results: Student performance on high-stakes examinations after active learning sessions on content and concepts had statistically higher average percentages on the second, third and fourth examinations. The average Diff (p) for the second, third, and fourth examination to the questions being considered for the study were (Diff p= 0.84, 0.83, and 0.92) with a positive moderate correlation for the second examination (r= 0.535) and strong positive correlation for the third and fourth examination (r=0.745 and r=0.856) for their final biochemistry grades. Conclusion: The study shows some positive and significant results that active learning methods are a useful and meaningful way to deliver a curriculum for a competency-based education system, and may be better suited than traditional lectures for providing content and assessing competencies which are necessary to become a complete physician.